2023
DOI: 10.3389/fneur.2023.1120150
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel outcomes at different stages of treatment in people with focal and generalized epilepsy treated in clinical practice: Evidence from the PERMIT study

Abstract: IntroductionThe PERMIT study is the largest pooled analysis of perampanel (PER) clinical practice data conducted to date.MethodsThis post-hoc analysis of PERMIT investigated the effectiveness, safety and tolerability of PER when used as early add-on therapy (after failure of one or two previous antiseizure medications) in comparison with late add-on therapy (after failure of three or more previous antiseizure medications). Retention and effectiveness were assessed after 3, 6, and 12 months, and at the last vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Patients in our study had a 67.9 50% responder rate and a 30.5% seizure-freedom rate during the 6-month maintenance, these results were in line with previous studies on perampanel early add-on ( 35 , 37 39 ). In addition, consistent with previous studies reporting higher efficacy of perampanel add-on in patients with FBTCS compared to those without FBTCS ( 14 , 19 , 38 , 40 ), we also found that perampanel was especially effective in patients with FBTCS, with a 50% responder rate of 96.0% and seizure-freedom rate of 76.0% during maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…Patients in our study had a 67.9 50% responder rate and a 30.5% seizure-freedom rate during the 6-month maintenance, these results were in line with previous studies on perampanel early add-on ( 35 , 37 39 ). In addition, consistent with previous studies reporting higher efficacy of perampanel add-on in patients with FBTCS compared to those without FBTCS ( 14 , 19 , 38 , 40 ), we also found that perampanel was especially effective in patients with FBTCS, with a 50% responder rate of 96.0% and seizure-freedom rate of 76.0% during maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…3 ) and the results of the descriptive analysis (Fig. 2 a), several publications highlight psychobehavioral symptoms in addition to dizziness, unsteadiness, and concentration problems as frequently reported AEs and reasons for therapy discontinuation [ 11 , 52 58 ]. Analogous to other ASMs, the occurrence and severity of AEs associated with PER appear to be dose-dependent [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, if we had considered all PWE lost to follow‐up as discontinuers, as was sometimes done in other studies, 48 the retention rate would still have been 71.5%, which is well within the range of other ASMs and the retrospective real‐world studies about CNB therapy. 16 , 17 , 19 , 20 , 23 , 24 , 26 , 30 , 31 , 32 , 48 , 49 , 50 , 51 , 52 , 53 …”
Section: Limitationsmentioning
confidence: 99%